2016
DOI: 10.1589/jpts.28.2260
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between accelerometry and clinical balance testing in stroke

Abstract: [Purpose] The purpose of this study was to determine the correlation between the Berg Balance Scale (BBS) and acceleration of postural sway in the Clinical Test of Sensory Interaction and Balance (CTSIB) by using a triaxial accelerometer for quantitative assessment. [Subjects and Methods] Twenty-seven stroke patients participated in this study. Balance ability was evaluated with the BBS, and postural sway was evaluated with a triaxial accelerometer. The data were then analyzed for frequency and correlation by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Postural sway can be expressed as the velocity moment of the center of gravity 7 ) . The increase of the velocity moment in each direction indicates a lower balance ability 8 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Postural sway can be expressed as the velocity moment of the center of gravity 7 ) . The increase of the velocity moment in each direction indicates a lower balance ability 8 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the psychometric properties of accelerometers, in two studies, the authors indicated that the purpose was to evaluate reliability [21,22], although one studied validity [22]. Three studies analyzed reliability and validity [23][24][25], two studies only analyzed validity [26,27] and one study did not specifically state a purpose [28].…”
Section: Methodsmentioning
confidence: 99%
“…In relation to validity, five studies employed a case-control design (the performance of healthy subjects was compared with that of people with experienced stroke in balance tests) [22,24,25,27,28], and three studies used a convergent validity design (analyzed the concordance between measures) [23,25,26] to study the criteria validity of accelerometers.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations